Research and Application Analysis of Scenario-Based Electronic Channels for Enterprise Customers - Meng Zhao (Dianxin kexue)
According to the research of enterprise customer electronic channels based on different scene modes, the development of electronic channels for enterprise customers and the applications in telecom carriers were analyzed. The situation with the inter industry were compared, and the development and application mode of scenario-based electronic channels for enterprise customers was put forward.